Integration of P5-PPRA Values as the Foundation of Islamic Pluralism in Islamic Religious Education Learning at MAN 2 Probolinggo City - Syarifah, Hasnia Imroatis; Choridah, Rifka Arifatul (Proceeding of International Conference on Islamic Education (ICIED), 2025)
MAN 2 Probolinggo City provides a microcosm of Islamic intra-religious diversity in Indonesia, housing students from backgrounds such as Nahdlatul Ulama (NU), Muhammadiyah, LDII, and Shia. Despite disparities in worship rituals and religious orientations, the madrasah successfully cultivates a harmonious learning atmosphere free from truth-claims and sectarian biases. This study intends to: (1) explore PAI teachers’ perception of Islamic pluralism in connection to P5–PPRA values; (2) identify P5–PPRA values that support Islamic pluralism; and (3) analyze the integration of these values within PAI instructional methods. Using a qualitative case study design, data were acquired through classroom observations, in-depth interviews, and document analysis. The findings reveal that PAI teachers possess a thorough and moderate knowledge of Islamic pluralism, considering differences among NU, Muhammadiyah, LDII, and Shia as part of sunnatullah that must be accepted and controlled properly. Mutual cooperation, tolerance, humanism, critical thinking, and rahmatan lil-’alamin are among the P5-PPRA qualities that were found to support pluralism. These values are integrated into PAI learning through collaborative teaching methods, holistic evaluation of cognitive and behavioral competencies, teacher-led efforts to build students’ motivation and confidence, equitable participation without discrimination, and the use of P5–PPRA as an ethical foundation for classroom culture. Overall, PAI learning at MAN 2 Probolinggo City indicates a good synergy between P5–PPRA and Islamic pluralism, molding students’ religious character to be inclusive, tolerant, and socially just.